2018
DOI: 10.2147/jir.s174982
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in irritable bowel syndrome (IBS)

Abstract: Irritable bowel syndrome (IBS) is a complex, functional gastrointestinal disorder characterized by chronic abdominal pain or discomfort and altered bowel habits. Despite the global prevalence and disease burden of IBS, its underlying pathophysiology remains unclear. Inflammation may play a pathogenic role in IBS. Studies have highlighted the persistence of mucosal inflammation at the microscopic and molecular level in IBS, with increased recruitment of enteroendocrine cells. Substantial overlaps between IBS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(199 citation statements)
references
References 44 publications
2
162
0
11
Order By: Relevance
“…32 Ng QX et al indicated that chronic, low-grade, and subclinical inflammation is not only related to the course of IBS disease but also considered as a continuation of IBS symptoms. 49 Our results support this finding because we observed that the PRDX1 and TNF-α levels (related to inflammation) in the group with the most severe symptoms were significantly higher than those in the groups with mild and moderate symptoms in the general IBS population (especially those with IBS-D and PI-IBS). In addition, we demonstrated for the first time that PRDX1 levels in peripheral circulation and colonic mucosa were associated with the severity of IBS symptoms, suggesting that IBS, particularly IBS-D and PI-IBS, is associated with systemic and local inflammatory responses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…32 Ng QX et al indicated that chronic, low-grade, and subclinical inflammation is not only related to the course of IBS disease but also considered as a continuation of IBS symptoms. 49 Our results support this finding because we observed that the PRDX1 and TNF-α levels (related to inflammation) in the group with the most severe symptoms were significantly higher than those in the groups with mild and moderate symptoms in the general IBS population (especially those with IBS-D and PI-IBS). In addition, we demonstrated for the first time that PRDX1 levels in peripheral circulation and colonic mucosa were associated with the severity of IBS symptoms, suggesting that IBS, particularly IBS-D and PI-IBS, is associated with systemic and local inflammatory responses.…”
Section: Discussionsupporting
confidence: 87%
“…35 Arjuna P provided evidence for subclinical intestinal mucosal inflammation in patients with IBS-D in a tropical setting. 49 Our results support this finding because we observed that the PRDX1 and TNF-α levels (related to inflammation) in the group with the most severe symptoms were significantly higher than those in the groups with mild and moderate symptoms in the general IBS population (especially those with IBS-D and PI-IBS for patients with IBS-D. 47 Keren's study also indicated that IBS-D is closely related to low-grade inflammation; however, the limitation is that only subtypes IBS-D and IBS-C were observed in their study. 49 Our results support this finding because we observed that the PRDX1 and TNF-α levels (related to inflammation) in the group with the most severe symptoms were significantly higher than those in the groups with mild and moderate symptoms in the general IBS population (especially those with IBS-D and PI-IBS for patients with IBS-D. 47 Keren's study also indicated that IBS-D is closely related to low-grade inflammation; however, the limitation is that only subtypes IBS-D and IBS-C were observed in their study.…”
Section: Correlation Of Ibs-sss With Prdx1 and Tnf-α In Patients Wimentioning
confidence: 99%
“…Multiple biological systems have been implicated in IBS pathophysiology [11]: differences have been discovered between IBS patients and healthy controls in inflammation pathways, the immune system, the GI epithelial barrier, the GI microbiota, the hypothalamic-pituitary-adrenal axis, cognitive areas of the central nervous system, and the enteric nervous system [12]. These differences have been presumed to lead to the manifestation of classical IBS symptoms such as visceral hypersensitivity (linked to recurrent abdominal pain) and altered GI motility [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 IBS is not a single disease entity but a heterogenous group of disorders encompassing a spectrum of pathophysiological mechanisms and clinical presentations. While traditionally regarded as a functional disorder without definitive structural or biochemical abnormalities, emergent evidence now challenges this concept and suggests that multiple processes including disordered brain-gut interaction, post-infectious changes, low-grade mucosal immune activation, 5 alterations in the gut microbiome, dysregulation of serotonin signaling and bile salt metabolism, and genetic factors likely contribute to the development and maintenance of IBS. 6 Based on bowel habit pattern, IBS may be grouped into one of four subtypes: IBS with predominant diarrhea (IBS-D), IBS with predominant constipation (IBS-C), IBS with mixed bowel habits (IBS-M) or IBS unclassified (IBS-U).…”
Section: Introductionmentioning
confidence: 99%